2017
DOI: 10.1063/1.5004244
|View full text |Cite
|
Sign up to set email alerts
|

Noise reduction in heat-assisted magnetic recording of bit-patterned media by optimizing a high/low Tc bilayer structure

Abstract: It is assumed that heat-assisted magnetic recording (HAMR) is the recording technique of the future. For pure hard magnetic grains in high density media with an average diameter of 5 nm and a height of 10 nm the switching probability is not sufficiently high for the use in bit-patterned media. Using a bilayer structure with 50% hard magnetic material with low Curie temperature and 50% soft magnetic material with high Curie temperature to obtain more than 99.2% switching probability, leads to very large jitter.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
1
10
1
Order By: Relevance
“…This result differs from the optimized material composition in Ref. [21], where the optimal composition consists of 80% hard magnetic and 20% soft magnetic materials. In Figure 4, a switching probability phase diagram of the optimized bilayer structure with 50% hard and 50% soft magnetic material can be seen.…”
Section: B Media Optimizationcontrasting
confidence: 89%
See 1 more Smart Citation
“…This result differs from the optimized material composition in Ref. [21], where the optimal composition consists of 80% hard magnetic and 20% soft magnetic materials. In Figure 4, a switching probability phase diagram of the optimized bilayer structure with 50% hard and 50% soft magnetic material can be seen.…”
Section: B Media Optimizationcontrasting
confidence: 89%
“…A work to reduce noise in recording media by optimizing a high/low T c bilayer structure (see Ref. [21]) showed that an optimial bilayer structure consists of 80% hard magnetic and 20% soft magnetic material. However, in the former work the Gilbert damping was assumed to be α HM = 0.1 which is hard to achieve in a FePt like hard magnetic material in reality.…”
Section: Introductionmentioning
confidence: 99%
“…This material configuration can be seen in Figure 1(a) and was already studied in former works. [9][10][11] Secondly, a grain consisting of two identical layers FePt is considered where the only difference is the peak temperature of the applied heat pulse. Hereby, the peak temperature of the heat pulse applied to the top layer is assumed to be 20% larger than that applied to the bottom layer (see Figure 1(b)).…”
Section: A Variation Of T Peakmentioning
confidence: 99%
“…P max and σ d are clearly two parameters with significant impact on the SNR, so it is recommendable to consider those values in terms of material optimization as in Ref. [5]. Furthermore the variation of two parameters simultaneously lead to SNR contours as in Fig.…”
Section: A Snr Curvesmentioning
confidence: 99%
“…In Ref. [5] for instance, the shape of the phase diagram depending on the composition of a bilayer material is investigated. This information only refers to a single grain but a priori tells very little about the resulting SNR of the read-back signal of a bit series.…”
Section: Introductionmentioning
confidence: 99%